A critical review of global decarbonization scenarios: what do they tell us about feasibility?. (6th November 2014) - Loftus, Peter J.; Cohen, Armond M.; Long, Jane C. S.; Jenkins, Jesse D.
<x xml:space="preserve">Abstract</x> Dozens of scenarios are published each year outlining paths to a low carbon global energy system. To provide insight into the relative feasibility of these global decarbonization scenarios, we examine 17 scenarios constructed using a diverse range of techniques and introduce a set of empirical benchmarks that can be applied to compare and assess the pace of energy system transformation entailed by each scenario. In particular, we quantify the implied rate of change in energy and carbon intensity and low‐carbon technology deployment rates for each scenario and benchmark each against historical experience and industry projections, where available. In addition, we examine how each study addresses the key technical, economic, and societal factors that may constrain the pace of low‐carbon energy transformation. We find that all of the scenarios envision historically unprecedented improvements in energy intensity, while normalized low‐carbon capacity deployment rates are broadly consistent with historical experience. Three scenarios that constrain the available portfolio of low‐carbon options by excluding some technologies (nuclear and carbon capture and storage) a priori are outliers, requiring much faster low‐carbon capacity deployment and energy intensity improvements. Finally, all of the studies present comparatively little detail on strategies to decarbonize the industrial and transportation sectors, and most give superficial treatment to relevant constraints on energy system transformations. To be reliable guides for policymaking, scenarios such as these need to be supplemented by more detailed analyses realistically addressing the key constraints on energy system transformation. WIREs Clim Change 2015, 6:93–112. doi: 10.1002/wcc.324 For further resources related to this article, please visit the WIREs website. Conflict of interest: The authors have declared no conflicts of interest for this article.